Bone mineral properties and 3D orientation of human lamellar bone around cement lines and the Haversian system. (2023) - Grünewald, T. A.; Johannes, A.; Wittig, N. K.; Palle, J.; Rack, A.; Burghammer, M.; Birkedal, H.
No abstract available